Basics of thermodynamics and phase transitions in complex intermetallics - Belin-Ferré, Esther (Book series on complex metallic alloys, 2008)
Complex metal alloys (CMAs) comprise a huge group of largely unknown alloys and compounds, where many phases are formed with crystal structures based on giant unit cells containing atom clusters, ranging from tens of to more than thousand atoms per unit cell. In these phases, for many phenomena, the physical length scales are substantially smaller than the unit-cell dimension. Hence, these materials offer unique combinations of properties which are mutually exclusive in conventional materials, such as metallic electric conductivity combined with low thermal conductivity, good light absorption with high-temperature stability, high metallic hardness with reduced wetting by liquids, etc. This book is the first of a series of books issued yearly as a deliverable to the European Community of the School established within the European Network of Excellence CMA. Written by reputed experts in the fields of metal physics, surface physics, surface chemistry, metallurgy, and process engineering, this book brings together expertise found inside as well as outside the network to provide a comprehensive overview of the current state of knowledge in CMAs.